Analysis of the persistence time of the SARS-CoV-2 virus in the cadaver and the risk of passing infection to autopsy staff. (March 2021) - Aquila, Isabella; Ricci, Pietrantonio; Bonetta, Carlo Filippo; Sacco, Matteo Antonio; Longhini, Federico; Torti, Carlo; Mazzitelli, Maria; Garofalo, Eugenio; Bruni, Andrea; Trecarichi, Enrico Maria; Serapide, Francesca; Gratteri, Santo; et al.
The activity of the SARS-CoV-2 virus has not yet been studied in a post-mortem setting. The absence of these data has led to the prohibition of exposure of infected corpses during burial procedures. Our aim was to assess the virus's persistence and the possibility of transmission in the post-mortem phase including autopsy staff. The sample group included 29 patients who were admitted to our Covid-19 Centre who died during hospitalisation and the autopsy staff. All the swabs were subjected to a one-step real-time reverse transcription polymerase chain reaction with cycle threshold (Ct) values. Swab collection was performed at 2 h, 4 h, 6 h, 12 h, over 24 since death. The following were the analysis of patients' swabs: 10 cases were positive 2 h after death; 10 cases positive 4 h after death; 9 cases were found positive 6 h after death; 7 cases positive 12 h after death; 9 cases remained positive 24 h after death. The swabs performed on all the forensic pathologist staff on duty who performed the autopsies were negative. The choice to avoid rituals and the display of corpses before and at the burial procedures given appears cautiously valid due to the persistence of the SARS-CoV-2 virus in the post-mortem period. Although the caution in choosing whether or not to perform an autopsy on infected corpses is acceptable, not to perform autopsies is not biologically supported.